PENINGKATAN PENGETAHUAN TENTANG HIGINE DAN SANITASI SERTA IMPLEMENTASINYA PADA PEDAGANG KULINER KAKI LIMA, PADA PUSAT KULINER DI KELURAHAN PUNIA KOTA MATARAM - Taufiq Chaidir (https://jurnal.fe.unram.ac.id/index.php/abdimas/about/privacy, 2021)
One of the primary human needs is food, therefore everyone must be able to fulfill it properly, meaning that food must not only be sufficient, but also the most important thing is to be able to provide nutritional intake and also must be hygienic and processing must pay attention to sanitation. The purpose of this community service is to increase the knowledge of culinary traders related to hygiene and sanitation in the food and beverage production process and traders can implement knowledge so that the resulting production can meet Law No. 32 on health. The method of implementing community service used is firstly observing targets related to the production process in producing culinary delights, secondly delivering the material, then continuing with discussions and forming a group team/officer who will monitor and evaluate the implementation of hygiene and sanitation principles in the production process carried out. by the merchant. The results of the service show that first, participants do not know what is meant by hygiene and sanitation and their effect on the products produced. This can be seen from the production process carried out on the floor, waste water disposal is still in an open channel, food storage is still mixed between food ingredients and finished food. Second, when the products sold to buyers do not meet the standards for selling food and beverages, this can be seen from the number of traders who do not cover food and drinks properly. Besides that, taking food does not use certain tools such as spoons.